Pre-operative anxiety in patients undergoing different types of surgery Comparative study - Rasoul Al-Yasiri, Abdul- (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Major life changes are among many factors that cause emotional arousal and anxiety ,and one of these changes is surgery. emotional reactions to surgery have specificeffects on the intensity and velocity as well as the process of physical disease and on the general state of wellbeing of the patient.Aims: This study is aimed at determining the relationship between the nature, extent and severity of preoperative anxiety and different types of surgery. Methods: 150 patients 84 males 68 females awaiting different types of surgery at Al-Kindy teaching hospital at the period from 1st January to 1stJuly 2008 were assessed for a clinicallydetected preoperative anxiety in relation to different variable including sex, age, type of surgery ,severity and the main fears related to the operation. Using general healthquestionnaires ( GHQs ) followed by semi-structured interview based on DSM-IV classification, and then mental state examination.Results: The study indicated that preoperative anxiety is common and is more in females, more in patients in their thirties and forties,it is in excess and is more sever in cardio-thoracicand gastro-intestinal tract surgery and is at its lowest level and severity in ophthalmology and ENT surgery. so also the fear of death is associated more with cardio-thoracic and GITsurgery. Females had more anxiety in all types of surgery except cardio-thoracic surgery which is more in males.Conclusions: Prevalence of Preoperative anxiety is high and represents over 2/3 of the sample and is more in rate and severity in surgery with uncertain outcome or being considered asmore risky by patients. Recommendations: The need for further studies on the effects of this anxiety on the post operative course and outcome, and the need for the training of paramedical staff in surgical wards on preoperative anxiety and ways of its intervention.